On studying ageism in long-term care: a systematic review of the literature - São José, José (2019)
Background: Ageism in long-term care is pervasive, but it is not easy to define, to identify and to fight it in practice. These difficulties could be overcome if we develop research capable to conceptualize, detect, measure, and understand the multidimensionality and complexity of ageism. Nevertheless, to achieve this, it is fundamental to know how ageism in long-term care has been previously studied. Methods: This paper systematically reviews studies on ageism in long-term care services published before October 2015 and indexed in Web of Science, PubMed, and Social Care Online electronic databases. Electronic searches were complemented with visual scanning of reference lists and hand searching of leading journals in the field of gerontology. Four specific review questions were addressed: Which analytical angles (aetiology, prevalence, manifestations, consequences, and interventions) have been explored? Which theories and concepts have been used? Which methods have been employed? Which variants of ageism have been covered? Results: Studies have focused mainly on the manifestations, etiology, and prevalence of ageism, neglecting its consequences and the interventions to tackle it; a significant number of studies used scales of ageism which, despite being appropriate considering the aims of the research, present important limitations; most studies have focused on residential services, neglecting non-residential services; some of the variants of ageism have been well covered, while implicit and self-ageism have been under-explored. Conclusions: Research on ageism in long-term care services is scarce but important. Much has been done but much remains to be done. An agenda for future research is presented.